14-3-3 and enolase abundances in the CSF of Prion diseased rats. Issue 3 (4th July 2018) - Gushue, Danielle; Herbst, Allen; Sim, Valerie; McKenzie, Debbie; Aiken, Judd M.
ABSTRACT: Creutzfeldt-Jakob disease (CJD) is characterized by an extended asymptomatic preclinical phase followed by rapid neurodegeneration. There are no effective treatments. CJD diagnosis is initially suspected based upon the clinical presentation of the disease and the exclusion of other etiologies. Neurologic symptoms are assessed in combination with results from cerebrospinal fluid (CSF) biomarker abundances, electroencephalography (EEG), magnetic resonance imaging (MRI), and in some countries, real-time quaking-induced conversion (RT-QuIC). Inconsistencies in sensitivities and specificities of prion disease biomarker abundance in CSF have been described, which can affect diagnostic certainty, but the utility of biomarkers for prognosis has not been fully explored. The clinical presentation of CJD is variable, and factors such as prion protein polymorphic variants, prion strain, and other genetic or environmental contributions may affect the disease progression, confounding the appearance or abundance of biomarkers in the CSF. These same factors may also affect the appearance or abundance of biomarkers, further confounding diagnosis. In this study, we controlled for many of these variables through the analysis of serial samples of CSF from prion-infected and control rats. Prion disease in laboratory rodents follows a defined disease course as the infection route and time, prion strain, genotype, and environmental conditions are all controlled. We measured the relative abundance of 14-3-3 and neuron-specific enolase (NSE) in CSF during the course of prion infection in rats. Even when disease-related, environmental and genetic variables were controlled, CSF 14-3-3 and NSE abundances were variable. Our study emphasizes the considerable diagnostic and prognostic limitations of these prion biomarkers.